Las instituciones supremas de auditoría y las iniciativas de anticorrupción - Murphy, David S. (2009)
This article begins with a review of the effect of public sector corruption and its causes. It explains the role of supreme audit institutions (SAI) in anti-corruption initiatives. The author ends with strategic recommendations for anti-corruption initiatives within SAIs including reducing the opportunities and incentives for corruption, increasing the cost of corrupt behavior and changing public expectations that cases of corruption will be successfully prosecuted.